Comparative Analysis of Biodiesels from Calabash and Rubber Seeds Oils - Awulu, J.O.; Ogbeh, G.O.; Asawa, N.D. (Center of Biomass & Renewable Energy, Diponegoro University, 2015)
Physicochemical properties of biodiesel from vegetable oils depend on the inherent properties of the oil-producing seeds. The purpose of this study is to investigate the physicochemical properties of biodiesels extracted from calabash and rubber seeds oils, as well as their combined oil mixtures with a view to ascertaining the most suitable for biodiesel production. Calabash and rubber seeds oils were separately extracted through the use of a mechanical press with periodic addition of water. Biodiesels were produced from each category of the oils by transesterification of the free fatty acid (FFA) with alcohol under the influence of a catalyst in batch process. The physicochemical properties of the biodiesels were investigated and comparatively analysed. The results obtained indicated an average of 1.40 wt% FFA for biodiesel produced from the purified calabash oil, which has a specific gravity of 0.920, pH of 5.93, flash point of 116 0C, fire point of 138 0C, cloud point of 70 0C, pour point of -4 0C, moisture content of 0.82 wt% and specific heat capacity of 5301 J/kgK. Conversely, the results obtained for biodiesel produced from the purified rubber oil showed an average of 33.66 wt% FFA, specific gravity of 0.885, pH of 5.51, flash point of 145 0C, fire point of 170 0C, cloud point of 10 0C, pour point of 4 0C, moisture content of 1.30 wt% and specific heat capacity of 9317 J/kgK. However, results obtained for biodiesel produced from the combined oil mixtures indicated an average of 19.77 wt% FFA content, specific gravity of 0.904, API gravity of 25.036, pH value of 5.73, flash point of 157 0C, Fire point of 180 0C, cloud point of 9 0C, pour point of 5 0C, moisture content of 0.93 wt% and specific heat capacity of 6051 J/kgK. Biodiesel produced from calabash seed oil is superior in quality to rubber seed oil, particularly in terms of its low FFA and moisture contents.